2008
DOI: 10.1097/mca.0b013e3282f35901
|View full text |Cite
|
Sign up to set email alerts
|

Total blush score: a new index for the assessment of microvascular perfusion in idiopathic dilated cardiomyopathy

Abstract: In IDC, decreased TBS might be assumed to be a surrogate marker for a diseased microvascular network in the catheterization laboratory. The relationship between reduced TBS and IDC severity suggests that this index might have prognostic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Besides, we used a new index proposed by Atmaca et al ., the TMBS. It was obtained by summing up the MBG of each coronary area . On the basis of Atmaca et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, we used a new index proposed by Atmaca et al ., the TMBS. It was obtained by summing up the MBG of each coronary area . On the basis of Atmaca et al .…”
Section: Methodsmentioning
confidence: 99%
“…Besides, we used a new index proposed by Atmaca et al, the TMBS. It was obtained by summing up the MBG of each coronary area [1]. On the basis of Atmaca et al's experience, we intended to evaluate another index: the TTFC, which was obtained from the sum of the TFCs of the three coronary arteries.…”
Section: Angiography Indices: Tfc and Mbgmentioning
confidence: 99%
“…Furthermore, Atmaca Y et al demonstrated how miscrovascular functionality can be impaired in patients with Syndrome X, through the computation of a new index defined "Myocardial Blush Grade", which evaluates the passage of the contrast mean through microvessels, visualized as a "blush" of the perfused territory, by counting the number of heart cycles required for it to fade out [11]. Moreover, they calculated a Total Myocardial Blush Score, defined as the sum of the MBG of each coronary territory, to define the overall microvascular functionality and verify its possible alterations in patients with dilatative cardiomiopathy and unharmed coronary trees [12]. Atmaca's and Gibson's surveys provided two diagnostic tools, demonstrating their correlation with an impaired microvascular capability to properly control coronary flow resistance.…”
Section: Angiographic Indices and Scintigraphic Imagesmentioning
confidence: 99%
“…Moreover we used a new index, proposed by Yusuf Atmaca et al, Total Myocardial Blush Score (TMBS), which consist of the sum of the myocardial blush grades of each coronary artery [13,14].…”
Section: Methodsmentioning
confidence: 99%